Computational modeling of cotranscriptional RNA folding - Lei Jin; Shi-Jie Chen (Computational and Structural Biotechnology Journal)
An RNA folds as it is transcribed. RNA folding during transcription differs fundamentally from thermodynamic folding. While thermodynamic folding reaches an equilibrium ensemble of structures, cotranscriptional folding is a kinetic process where the RNA structure evolves as the chain elongates during transcription. This dynamic folding pathway causes cotranscriptional structures often to deviate from thermodynamic predictions, as the system rarely reaches equilibrium. Since these cotranscriptional effects can persist in the mature RNA's structure, understanding this kinetic process is crucial. While experimental studies of cotranscriptional folding have been successful, they remain resource-intensive. Computational modeling has emerged as an increasingly practical and powerful approach for investigating these dynamics. This short review examines current computational methods and tools for simulating cotranscriptional folding, with the goal of advancing our understanding of RNA folding mechanisms.